(untitled) (Journal of Global Accounting, 2024)
This study aims to determine the effect of employee welfare and occupational health and safety reporting on audit quality of listed non-financial firms in Nigeria. The study used an Ex-Post Facto research design. Ninety five companies as of December 2022 that were listed on the Nigeria Exchange Group make up the study’s population. A purposive sampling technique was adopted in selecting the seventy four listed non-financial firms that form the unit of analysis for this study. The panel data were derived from company’s annual reports and accounts with the Nigeria Exchange Group Factbook for the period of eleven years spanning from 2012 to 2022. The ordinary least square statistical technique was adopted in the analysis of data with the aid of E-View 10.0 Software. The study revealed that occupational health and safety and employees’ welfare has no significant effect on audit fees. The study recommends among others that managers might need to focus more on providing the needs of their employees by improving on its disclosure on occupational health and safety and employee welfare in their reporting.